Anotação de corpus: caracterização de Entidades Nomeadas em tweets do mercado financeiro - Piai, Laís (2025)
Corpus annotation is a cornerstone of Natural Language Processing (NLP), providing the foundation for training and evaluating Machine Learning systems, as well as for investigating linguistic behavior in various domains. A key challenge in this area is the annotation of Named Entities (NEs) in user-generated content (UGC). The informal language and a wide range of platform and domain-specific phenomena found in tweets demand highly adapted annotation methodologies. This dissertation addresses this challenge by conducting an independent reannotation of the DANTEStocks, a Portuguese corpus of 4,048 financial market tweets (84,396 tokens). While a previous annotation based on the 10 general categories of the Second HAREM existed, our work expands this taxonomy to a more granular set of 47 types. This was achieved by refining the original guidelines based on linguistically motivated decisions and by introducing four new domain-specific types: certificate, indicator, ticker, and user. The annotation was carried out by a single annotator using a semi-automatic approach that combined rule-based methods with manual curation, resulting in a new reference annotation and a comprehensive set of guidelines. The resulting annotation comprises 20,092 entities (24,825 tokens). A detailed characterization of the corpus revealed a linguistic profile dominated by single-token (i.e. those consisting of a single word) entities and by specific stock market types such as ticker, money, and virtual. The main contributions of this work are therefore: the enrichment of the DANTEStocks corpus with a fine-grained NE annotation, a set of guidelines for annotating UGC, and a discussion of the strategies developed to overcome the inherent challenges of this task.